Advanced Eco-friendly Wood-Based Composites - Reh, Roman; Kristak, Lubos; Antov, Petar (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In collaboration with the MDPI publishing house, we are pleased to introduce the reader to our new project, a Special Issue entitled "Advanced Eco-friendly Wood-Based Composites". This Special Issue provides an opportunity to investigate advanced eco-friendly wood-based composites from a broader perspective. The coronavirus pandemic and shutdown measures employed to contain it, as well as the ongoing war in Ukraine, have influenced and decelerated the world economy and adversely impacted research activities on most levels in all countries. Surprisingly, researchers in the field of wood-based composites have continued to make progress, which is also described in this Special Issue.